PRINCIPAL’S ATTITUDE TO THE EXPANSION OF THE AUTONOMY OF THE INSTITUTION OF GENERAL SECONDARY EDUCATION: THE RESULTS OF ANALYTICAL RESEARCH - Kostiantyn Lynov (Borys Grinchenko Kyiv University, 2021)
The authors of the article analyze the results of a survey of school principals conducted in December 2020 in Kyiv. The Law of Ukraine «On Education» provides for granting educational institutions the right to expand the scope of autonomy, namely – academic, organizational, personnel and financial autonomy. This process, among other things, depends on the level of readiness of the principals for self-government at school, the desire and ability to use the opportunities provided by the legislation of Ukraine.